Les Mégalithes du département du Morbihan : Structures Funéraires et Pierres Dresses - Gouézin, Philippe (Archaeopress, 2022)
Based on a corpus of architectural plans comprising 1413 megalithic monuments from the Department of Morbihan, including more than 250 unpublished monuments, this book aims at a better understanding of megalithism, or more precisely megalithisms, and presents a new approach to the relationship between standing stones (menhirs) and tombs (dolmens).
Description based upon print version of record.
Figure 26 Graphique du rapport largeur / épaisseur des pierres dressées isolées.
Keywords: Megalithic monuments -- France -- Morbihan.; Morbihan (France) -- Antiquities.; Monuments mégalithiques -- France -- Morbihan.; Prehistoric archaeology.; SOCIAL SCIENCE -- Archaeology.; Antiquities; Megalithic monuments; France -- Morbihan